Evaluation of online learning system acceptance in Kolej Poly-Tech Mara Ipoh / Haslina Hisham - Hisham, Haslina (2012)
According to Teo (2011), teachers play an important role in integration of technology in teaching and learning. However, when teachers do not use technology the way it was designed, the effective teaching and learning cannot be take place. It is found that 60% of lecturers in Kolej Poly-Tech MARA (KPTM) Ipoh are actively uses online learning system in their teaching and learning with others are used occasionally. Thus, the objective of this study is to identify the degree of lecturers' acceptance and factors that influence the acceptance of online learning system among lecturers in KPTM Ipoh. In addition, the objective of the study is also to provide the recommendation that contributes to the online learning system acceptance in educational institutions. Unified Theory of Acceptance and Use Technology (UTAUT) model is chosen as a fundamental theory of the research study. A quantitative research methodology is used based on a survey that was collected from 38 lecturers. Descriptive analysis and correlation analysis is used to analyze and interpret the collected data. The result shows that the degree of online learning system acceptance among lecturers is high with facilitating conditions is found as the strong factors that contribute to the lecturers' acceptance in online learning system. The result also demonstrates direct relationship between performance expectancy, effort expectancy and social influence with the intention of use of online learning system. Furthermore, it is also found that social influence has positive relationship with performance expectancy. The findings will help policy makers in educational institution to better understand the factor that influence lecturers' acceptance of online learning system.